2015
DOI: 10.1007/s00453-015-0061-3
|View full text |Cite
|
Sign up to set email alerts
|

Compositions into Powers of b: Asymptotic Enumeration and Parameters

Abstract: For a fixed integer base b ≥ 2, we consider the number of compositions of 1 into a given number of powers of b and, related, the maximum number of representations a positive integer can have as an ordered sum of powers of b. We study the asymptotic growth of those numbers and give precise asymptotic formulae for them, thereby improving on earlier results of Molteni. Our approach uses generating functions, which we obtain from infinite transfer matrices. With the same techniques the distribution of the largest … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…If * is the arithmetic, geometric, or harmonic mean, then s a n ( * ) = C n−1 for all n ≥ 1 (see Csákány, Waldhauser [5]). However, as we are going to show next, its ac-spectrum agrees with an interesting sequence in OEIS [19, A007178], which enumerates different ways to write 1 as an ordered sum of n powers of 2 (i.e., compositions of 1 into powers of 2) and is also related to the so-called prefix codes or Huffman codes (see, e.g., Even and Lempel [6], Giorgilli and Molteni [11], Knuth [12], Krenn and Wagner [13] and Lehr, Shallit and Tromp [14]). Proposition 4.4.…”
Section: 2supporting
confidence: 53%
“…If * is the arithmetic, geometric, or harmonic mean, then s a n ( * ) = C n−1 for all n ≥ 1 (see Csákány, Waldhauser [5]). However, as we are going to show next, its ac-spectrum agrees with an interesting sequence in OEIS [19, A007178], which enumerates different ways to write 1 as an ordered sum of n powers of 2 (i.e., compositions of 1 into powers of 2) and is also related to the so-called prefix codes or Huffman codes (see, e.g., Even and Lempel [6], Giorgilli and Molteni [11], Knuth [12], Krenn and Wagner [13] and Lehr, Shallit and Tromp [14]). Proposition 4.4.…”
Section: 2supporting
confidence: 53%
“…Krenn and Wagner [19] showed that the number of full-support dyadic distributions on X n is asymptotic to αγ n−1 n!, where α ≈ 0.296 and γ ≈ 1.193, implying that the number of dyadic distributions on X n is asymptotic to αe 1/γ γ n−1 n!. Boyd [4] showed that the number of monotone full-support dyadic distributions on X n is asymptotic to βλ n , where β ≈ 0.142 and λ ≈ 1.794, implying that the number of monotone dyadic distributions on X n is asymptotic to β(1 + λ) n .…”
Section: Reduction To Maximum Relative Densitymentioning
confidence: 99%
“…A. Sellers [76] and D. Krenn and S. Wagner [97] (which deals mostly with m-ary compositions). It is easy to see that the number f bp In conclusion of Section 3 and of our article we turn to cancellative problems related to the initial Example 5.…”
Section: Proofmentioning
confidence: 99%
“…A. Sellers [76] and D. Krenn and S. Wagner [97] (which deals mostly with m-ary compositions). It is easy to see that the number f bp (n) := f mp (n, 2) of binary partitions of n follows the recurrence f bp (0) = 1 and f bp (n) = f bp (n − 1) + f bp (n/2) for n ≥ 1 (where f bp (n/2) = 0 if n/2 ∈ N 0 ).…”
mentioning
confidence: 99%